USING INTERACTIVE METHODS TO TEACH COMPOSITION AND COLOR HARMONY - Abdurahmonova Dildora Nizomjon qizi (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
Abstract: This article explores the use of interactive methods in teaching composition and color harmony. It highlights pedagogical approaches that enhance students’ understanding of visual balance, color relationships, and compositional principles. Practical exercises, collaborative activities, and innovative teaching techniques are emphasized as effective strategies to engage students, develop their creative skills, and improve their aesthetic perception in fine arts education.